Her cup for sweet cacao food in ancient Maya society - Ardren, Traci 1966- (Linda Schele series in Maya and pre-Columbian studies, 2021)
These chapters, written by some of the leading scholars in the field, showcase a variety of approaches and present new evidence from faunal remains, hieroglyphic texts, chemical analyses, and art. Thoughtful and revealing, Her Cup for Sweet Cacao unlocks a more comprehensive understanding of how food was instrumental to the development of ancient Maya culture"--